2018
DOI: 10.1177/0143034317749888
|View full text |Cite
|
Sign up to set email alerts
|

How family socioeconomic status, peer behaviors, and school-based intervention on healthy habits influence adolescent eating behaviors

Abstract: Psychologists in schools can play an important role in developing policies and programs to promote healthy eating habits. This study analyses the contributions of family socioeconomic status, peer influence (schoolmates’ food consumption), and school-based nutrition interventions to explain adolescent eating behaviors. Data were obtained from the 2014 Health behaviour in school-aged children survey in Spain, with a sample of 6,851 adolescents (11- to 16-years-old). The results suggest that school-based healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…The positive association between parental education and S-HEI score found in the current study coincides with others reporting that parenteral education plays a role in the adoption of healthier eating behaviors [ 46 ]. Specifically, parental education was associated with an increased consumption of fruits and vegetables [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…The positive association between parental education and S-HEI score found in the current study coincides with others reporting that parenteral education plays a role in the adoption of healthier eating behaviors [ 46 ]. Specifically, parental education was associated with an increased consumption of fruits and vegetables [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, MD adherence was inversely correlated with age. This could be associated with the greater influence of peers with increasing age, alongside increases in autonomy and financial independence (18) . With regard to indicators of mental wellbeing, adolescents with greater MD adherence also reported higher levels of health-related quality of life and body satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, choices regarding food consumption can be determined at an individual level according to age, nationality, sex, preferences, nutritional knowledge, physiological state and psychological factors (15)(16)(17) . On the other hand, socio-cultural factors such as social norms, the influence of family and peers, socio-economic status, the media and social networks appear to play a mediatory role over dietary habits (18,19) . Finally, the influence of setting, in the same way as access to and availability of healthy foods, also intervenes in dietary choices (20) .…”
mentioning
confidence: 99%
“…In the present study, the socioeconomic status and the mother's schooling were not associated with the outcome. However, some authors demonstrated that not having breakfast frequently was significantly more common among children and adolescents with lower socioeconomic status or whose mothers had fewer years of schooling [11,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%